2016
DOI: 10.1371/journal.pone.0163952
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Ruminative Thinking in Adolescents at Risk for Depressive Relapse: Rumination-Focused Cognitive Behavior Therapy in a Pilot Randomized Controlled Trial with Resting State fMRI

Abstract: This pilot randomized control trial was designed to examine whether Rumination-Focused Cognitive Behavior Therapy (RFCBT) reduces rumination and residual depressive symptoms among adolescents with a history of Major Depressive Disorder (MDD) who are at risk for relapse. We also examined whether these changes in symptoms were associated with changes in functional connectivity of the posterior cingulate cortex (PCC), a key node in the default mode network (DMN). Thirty-three adolescents (ages 12–18) were randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 59 publications
3
67
0
Order By: Relevance
“…Alternatively, even if training in mindfulness or decentering does not directly alter these risk factors, the results of this study suggest that improving decentering could de-automatize emotional reactions to PC, and might reduce the risk conferred by PC and parasympathetic inflexibility. In addition, several existing treatments explicitly target PC, including rumination-focused CBT (Watkins et al, 2011; Jacobs et al, 2016), ERT (Mennin & Fresco, 2013b; Mennin et al, 2015), metacognitive therapy (Wells, 2012), and cognitive control training (Siegle et al, 2014). It is possible that these treatments also could be tailored for prevention to apply to individuals who are at risk, but do not have a history of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, even if training in mindfulness or decentering does not directly alter these risk factors, the results of this study suggest that improving decentering could de-automatize emotional reactions to PC, and might reduce the risk conferred by PC and parasympathetic inflexibility. In addition, several existing treatments explicitly target PC, including rumination-focused CBT (Watkins et al, 2011; Jacobs et al, 2016), ERT (Mennin & Fresco, 2013b; Mennin et al, 2015), metacognitive therapy (Wells, 2012), and cognitive control training (Siegle et al, 2014). It is possible that these treatments also could be tailored for prevention to apply to individuals who are at risk, but do not have a history of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Subsets of these samples have been reported in prior work, including from MH091811 awarded to Langenecker (Bessette et al, 2018;Bhaumik et al, 2017;DelDonno et al, 2017;Jacobs et al, 2014Jacobs et al, , 2016Jenkins et al, 2017;Rao et al, 2016;Stange et al, 2017), MH086517 awarded to Monk and Phan (Hamm et al, 2014;Wu et al, 2016), UIC CCTS UL1TR000050, Mind and Life Foundation, and Klingenstein Third Generation Foundation Fellowship awarded to Jacobs Peters et al, 2016). Data is also present from MH101487 (awarded to Langenecker).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In addition, greater temporal lobe cortical thickness has been found in MDD patients with anxiety than MDD patients without (Inkster et al, ). Interestingly, despite the association of increased temporal cortex‐PCC connectivity with rumination mentioned previously (Jacobs et al, ), a separate study found decreased connectivity between these regions in MDD (Yang et al, ). Regardless, there is evidence that inferior temporal cortex shows connectivity with the PCC in resting state (Uddin, Kelly, Biswal, Castellanos, & Milham, ); therefore, we believe our finding in this region further supports an interaction between 5‐HT 1A and the DMN.…”
Section: Discussionmentioning
confidence: 82%
“…Plausibility of this hypothesis is increased by the fact that patients with MDD tend to have higher 5‐HT 1A binding and cortical thickness in the PCC. Interestingly, a recent study has found that functional resting state connectivity between the PCC and inferior temporal cortex is also associated with rumination and depressive symptoms (Jacobs et al, ).…”
Section: Discussionmentioning
confidence: 99%